2022
DOI: 10.1371/journal.pone.0267831
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum improves LPS-induced Caco2 cell line intestinal barrier damage via cyclic AMP-PKA signaling

Abstract: Lactobacillus plantarum (LP) has been shown to exhibit protective effects on intestinal barrier function in septic rats, although the regulatory mechanism has not been established. We determined whether LP imparts such protective effects in a lipopolysaccharide (LPS)-induced Caco2 cell monolayer model and whether cAMP-PKA signaling is the underlying mechanism of action. The cyclic adenosine monophosphate (cAMP) agonist, forskolin (FSK), and the protein kinase A (PKA) inhibitor, HT89, were used to study the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The LPS induced the expected TEER reduction only in the absence of HMC-1.2 ( Figure 1 and Figure 2 ), indeed, it has been reported to impair tight junction strength [ 28 , 29 , 30 , 31 ] via TLR4-dependent activation of the membrane-associated adaptor protein focal adhesion kinase in Caco-2 monolayers [ 32 ]. Interestingly, we showed that both the exposure to the probiotic formulation for 24 h, and the presence of HMC-1.2, concurred to preserve the integrity of the epithelial layer, as demonstrated by the TEER values in the Caco-2/HT-29 co-cultures.…”
Section: Discussionmentioning
confidence: 79%
“…The LPS induced the expected TEER reduction only in the absence of HMC-1.2 ( Figure 1 and Figure 2 ), indeed, it has been reported to impair tight junction strength [ 28 , 29 , 30 , 31 ] via TLR4-dependent activation of the membrane-associated adaptor protein focal adhesion kinase in Caco-2 monolayers [ 32 ]. Interestingly, we showed that both the exposure to the probiotic formulation for 24 h, and the presence of HMC-1.2, concurred to preserve the integrity of the epithelial layer, as demonstrated by the TEER values in the Caco-2/HT-29 co-cultures.…”
Section: Discussionmentioning
confidence: 79%
“…Then we further investigated whether lidocaine can directly induce the expression of CRHR2 using Caco2 cells. LPS, a known disruptor of the intestinal barrier, is commonly used to simulate barrier damage in vitro 46 . The results showed that the expression of CRHR2 on Caco2 cells was impaired after LPS treatment but was boosted by supplemented with lidocaine (Figure 7A,B).…”
Section: Resultsmentioning
confidence: 97%
“…We utilized the in vitro co-culture sepsis model following LPS treatment based on a study by Wei et al [ 22 ]. The integrity of tight junction structures is a key factor in intestinal cell barrier function.…”
Section: Discussionmentioning
confidence: 99%